ICE RELEASE COMPOSITION, ARTICLE AND METHOD - YORKGITIS, ELAINE M; MELANCON, KURT C (1990)
60557-3825 The invention relates to an article capable of repeatedly releasing ice from a surface thereof which comprises a coating of a crosslinked organosilicone material on said surface, said coating resulting from the crosslinking of a composition containing (a) a polysiloxane having terminal ethylenically unsaturated groups (b) a polyhydrosiloxane, (c) a platinum- or other metal-containing hydrosilation catalyst in an amount sufficient to facilitate the crosslinking of said components (a) and (b), and optionally, (d) a nonfunctional polysiloxane free from ethylenic unsaturation, and optionally (e) an organic hydrosilation inhibitor in an amount sufficient to inhibit premature crosslinking of said composition at low temperature, but insufficient to inhibit crosslinking at elevated temperature, wherein said coating is present at a weight of at least 3 g/m2. The invention also relates to compositions and methods for assisting ice release. The invention finds use in prevention of ice build-up on the surfaces of such things as sign faces, signal transmission lines (e.g., telephone and electrical cables), automobiles, railroad cars, aircraft, heat exchange equipment, ice manufacturing facilities, buildings, transportation signs, roofing, snow removal equipment and the like.